Results of a 36‐year surveillance program for ulcerative colitis‐associated neoplasia in the Japanese population. Issue 2 (2nd November 2017) - Kishikawa, Junko; Hata, Keisuke; Kazama, Shinsuke; Anzai, Hiroyuki; Shinagawa, Takahide; Murono, Koji; Kaneko, Manabu; Sasaki, Kazuhito; Yasuda, Koji; Otani, Kensuke; Nishikawa, Takeshi; Tanaka, Toshiaki; et al.
Abstract : Background and Aim: Surveillance colonoscopy has been carried out for patients with long‐standing ulcerative colitis who have an increased risk for colorectal cancer. The aim of the present study was to determine the incidence of and the risk factors for neoplasia. Methods: We evaluated 289 ulcerative colitis patients who underwent surveillance colonoscopy between January1979 and December 2014. Cumulative incidence of neoplasia and its risk factors were investigated. Clinical stage and overall survival were compared between the surveillance and non‐surveillance groups. Results: Cumulative risk of dysplasia was 3.3%, 12.1%, 21.8%, and 29.1% at 10, 20, 30 and 40 years after the onset of ulcerative colitis, respectively. Cumulative risk of colorectal cancer was 0.7%, 3.2%, 5.2%, and 5.2% at 10, 20, 30 and 40 years from the onset of ulcerative colitis, respectively. Total colitis was a risk factor for neoplasia ( P = 0.015; hazard ratio, 2.96). Conclusions: Our surveillance colonoscopy program revealed the incidence and risk factors of ulcerative colitis‐associated neoplasias in the Japanese population. Total colitis is a risk factor for neoplasia.